2019
DOI: 10.3390/ma12213516
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ag2O Content on the Optical and Spectroscopic Properties of Fluoro-Phosphate Glasses

Abstract: Glasses with the system (84.60-x) NaPO3-5 ZnO-(9.40-x) NaF-x Ag2O-1 Er2O3, (x = 0, 2, 4, and 6) (mol%) were synthesized by the conventional melt-quenching method. The impact of the addition of Ag2O on the physical, thermal, structural, and optical properties of the glasses is discussed. The Judd-Oflet analysis was used to evaluate the radiative properties of the emission transitions of the glasses. The enhancement of luminescence properties due to Ag2O is discussed in terms of consequent changes in the local e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“… 28 The band at approximately 1250 cm −1 is associated with the asymmetric stretching vibration of P–O–P bonds, ν as (P–O–P). 26 Between 950 and 1030 cm −1 , multiple shoulders are detected and they were assigned to v s (PO 3 2− ) in Q 1 units. 29 According to the spectral data, an increase in the BaO content from 20 to 30 mol% results in a higher proportion of Q 2 units at the expense of Q 1 units.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 28 The band at approximately 1250 cm −1 is associated with the asymmetric stretching vibration of P–O–P bonds, ν as (P–O–P). 26 Between 950 and 1030 cm −1 , multiple shoulders are detected and they were assigned to v s (PO 3 2− ) in Q 1 units. 29 According to the spectral data, an increase in the BaO content from 20 to 30 mol% results in a higher proportion of Q 2 units at the expense of Q 1 units.…”
Section: Resultsmentioning
confidence: 99%
“…Within the spectra, a prominent band appearing around 890 cm −1 , indicating the asymmetric stretching vibration of P-O bonds, n as (P-O-P). 26,27 Around 1075 cm −1 , another signicant band arises, though the specic vibrational mode of v s (P-O-P) of both Q 2 and Q 1 units. 28 The band at approximately 1250 cm −1 is associated with the asymmetric stretching vibration of P-O-P bonds, n as (P-O-P).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it is reported that TeO 2 glasses have relatively high density and thus possess a good attenuation ability against gamma radiation [20][21][22]. During the preparation process of the TeO 2 -based glasses, some glasses modi ers such as ZnO and Ag 2 O are used to enhance their optical features and radiation attenuation competences [23,24]. Introducing the Er 2 O 3 ions enhances the chemical durability of glass as well as the radiation shielding features.…”
Section: Introductionmentioning
confidence: 99%